Influence of Government Policy on Climatic Changes: A Case Study of Kigezi Region South Western Uganda. - Maniraguha, Alex (Kabale University, 2023)
Climate changes in the Kigezi region south western Uganda were caused by man's endangering nature for example destruction of vegetation, occupation of wetlands, lumbering, industrial fumes, and many others. The government came up with policies to ensure that all stakeholders addressed climate change impacts and their causes through appropriate measures promoting sustainable development and a green economy for example, the Disaster Preparedness and Management Policy (DPM) 2010 the policy calls for proactive efforts to reduce the causes and the negative impacts of climate change, environmental policy(l995) that were the umbrella framework that recognized the importance of the conservation and restoration of ecosystems, biodiversity and ecological processes, Energy policy, 2002 the goal of the energy policy (2002) met the energy needs of the Ugandan population for social and economic development in an environmentally sustainable manner. The purpose of this study was to establish the means through which that situation was to be averted.